2014
DOI: 10.1186/1750-1326-9-53
|View full text |Cite
|
Sign up to set email alerts
|

SNAP-25 is a promising novel cerebrospinal fluid biomarker for synapse degeneration in Alzheimer’s disease

Abstract: BackgroundSynaptic degeneration is an early pathogenic event in Alzheimer’s disease, associated with cognitive impairment and disease progression. Cerebrospinal fluid biomarkers reflecting synaptic integrity would be highly valuable tools to monitor synaptic degeneration directly in patients. We previously showed that synaptic proteins such as synaptotagmin and synaptosomal-associated protein 25 (SNAP-25) could be detected in pooled samples of cerebrospinal fluid, however these assays were not sensitive enough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
208
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(225 citation statements)
references
References 40 publications
15
208
0
2
Order By: Relevance
“…Another advantage of our study is the relatively large number of cases with DLB and PDD, giving us more potential to mitigate the influence of the individual changes that occur in smaller cohorts. One limitation of our study is that our AD cohort was comprised of only 18 cases, however our results are in agreement with previous findings regarding SNAP25 as a promising biomarker for synapse degeneration in AD [41]. The availability of longitudinal standardized clinical data in brain bank studies is a relatively unique feature of our study though longitudinal MMSE scores were not available for all patients (Supplementary Table 1).…”
Section: Discussionsupporting
confidence: 73%
“…Another advantage of our study is the relatively large number of cases with DLB and PDD, giving us more potential to mitigate the influence of the individual changes that occur in smaller cohorts. One limitation of our study is that our AD cohort was comprised of only 18 cases, however our results are in agreement with previous findings regarding SNAP25 as a promising biomarker for synapse degeneration in AD [41]. The availability of longitudinal standardized clinical data in brain bank studies is a relatively unique feature of our study though longitudinal MMSE scores were not available for all patients (Supplementary Table 1).…”
Section: Discussionsupporting
confidence: 73%
“…It is therefore an important presynaptic marker of functional synapses. Consistent with the idea that early AD and cognitive impairment are highly correlated with synaptic dysfunction, SNAP25 was found to be decreased in the membrane-associated fractions derived from the brains of AD patients, whereas increased levels were observed in the CSF of early AD patients compared with normal control patients (60). These results suggest that SNAP25 is a good candidate biomarker for cognitive decline.…”
supporting
confidence: 79%
“…Several lines of evidence support the idea that A␤ oligomers are toxic to synapses and cells including proteomic studies (36,40,60,61,74). It has been proposed that A␤ oligomers interact with membrane receptors and the membrane itself to increase calcium and lipid peroxidation (14).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Based on this, it is conceivable that SEPT8 could play a central role at the synaptic level in the early stages of Alzheimer's-disease-related synaptotoxicity. It has been recently shown that protein affinity purification combined with mass spectrometry can be utilized for the identification of fragments of the presynaptic SNARE complex component synaptosomal-associated protein 25 (SNAP25) in the cerebrospinal fluid (Brinkmalm et al, 2014). Indeed, significantly increased levels of SNAP25 fragments have been observed in the cerebrospinal fluid of Alzheimer's disease patients even by the very early stages of the disease.…”
Section: Discussionmentioning
confidence: 99%